Production of functional, stable, unmutated recombinant human papillomavirus E6 oncoprotein: implications for HPV-tumor diagnosis and therapy. Issue 1 (December 2016) - Illiano, Elena; Demurtas, Olivia; Massa, Silvia; Bonito, Paola; Consalvi, Valerio; Chiaraluce, Roberta; Zanotto, Carlo; Giuli Morghen, Carlo; Radaelli, Antonia; Venuti, Aldo; Franconi, Rosella
Abstract Background High-risk human papillomaviruses (HR-HPVs) types 16 and 18 are the main etiological agents of cervical cancer, with more than 550, 000 new cases each year worldwide. HPVs are also associated with other ano-genital and head-and-neck tumors. The HR-HPV E6 and E7 oncoproteins are responsible for onset and maintenance of the cell transformation state, and they represent appropriate targets for development of diagnostic and therapeutic tools. Methods The unmutated E6 gene from HPV16 and HPV18 and from low-risk HPV11 was cloned in a prokaryotic expression vector for expression of the Histidine-tagged E6 protein (His6 -E6), according to a novel procedure. The structural properties were determined using circular dichroism and fluorescence spectroscopy. His6 -E6 oncoprotein immunogenicity was assessed in a mouse model, and its functionality was determined using in vitro GST pull-down and protein degradation assays. Results The His6 -tagged E6 proteins from HPV16, HPV18, and HPV11 E6 genes, without any further modification in the amino-acid sequence, were produced in bacteria as soluble and stable molecules. Structural analyses of HPV16 His6 -E6 suggests that it maintains correct folding and conformational properties. C57BL/6 mice immunized with HPV16 His6 -E6 developed significant humoral immune responses. The E6 proteins from HPV16, HPV18, and HPV11 were purified according to a new procedure, and investigated for protein–protein interactions. HR-HPV His6 -E6 bound p53, the PDZ1 motif from MAGI-1 proteins, the human discs large tumor suppressor, and the human ubiquitin ligase E6-associated protein, thus suggesting that it is biologically active. The purified HR-HPV E6 proteins also targeted the MAGI-3 and p53 proteins for degradation. Conclusions This new procedure generates a stable, unmutated HPV16 E6 protein, which maintains the E6 properties in in vitro binding assays. This will be useful for basic studies, and for development of diagnostic kits and immunotherapies in preclinical mouse models of HPV-related tumorigenesis.